Effectiveness of an Educational Program on Nurse’s Knowledge towards Neonatal Total Parenteral Nutrition: فاعلية برنامج تعليمي على معارف الممرضين والممرضات حول التغذية الوريدية الكلية لحديثي الولادة - Sakran, Aseel Ali; Al-Mosawi, Khatam (Iraqi National Journal of Nursing Specialties, 2024)
Objective(s): This study aims to evaluate the effectiveness of an educational program on nurse’s knowledge toward neonatal total parenteral.Methods: A quasi-experimental design has been used in the present studyconducted at Medical City Hospitals including Baghdad Teaching Hospital, Privat Nursing Home, and Pediatric Teaching Hospital from November 12th, 2022 to May 1st, 2023. A convenience sample of 55 nurses was chosen: (25) nurses were in the study group and (25) nurses were in the control group. Five nurses were excluded from the study sample as part of a pilot study. The data was analyzed and interpreted through the use of the application of Statistical Package for Social Sciences (SPSS), version 26.0.Results: This study shows that 80% of nurses in the study group and 58% of them in the control group reported their source of information is from books as reported by 76% of them in the study group and 68% of them in the control group. The study finding reveals that nurses in the study group had poor level of knowledge during the pre-test time (96%, M±SD= 28.80±1.871), while they are showing good level of knowledge during the post-test 1 (96%, M±SD= 68.92±1.352) and post-test 2 (92%, M±SD= 68.00±.1. 825.indicates significant change in nurses’ level of knowledge after applying the program.Conclusion: Nurses demonstrated a significant improvement in their knowledge following the implementation of the programme.Recommendations: Further research is recommended to explore the relationship between nurses’ demographic data and their knowledge and practice about parenteral nutrition. Also, Further study about applications of the same study to the nurses in the other pediatrics Hospitals.